Comments on Local cod (Gadus morhua) revealed by egg surveys and population genetic analysis after longstanding depletion on the Swedish Skagerrak Coast by Svedäng et al. (3rd June 2019) - Cardinale, Massimiliano; Mariani, Stefano; Hjelm, Joakim
Abstract: Svedäng et al. (2018) concluded that "the occurrence of locally spawned cod eggs suggests that spawning on the Swedish Skagerrak coast takes place, which belong to either a coastal subpopulation that is a remnant stock of a once much larger cod population, or a newly formed subpopulation that is now successfully inhabiting the coastal ecosystems along the Swedish Skagerrak coast". However, after carefully reviewing the results and the data presented by the authors, we were no longer convinced that the information presented provided enough evidence for a local, distinct, coastal cod population in the Swedish Skagerrak. Thus, we requested the original genotype data, which the authors kindly provided to us. This allowed us to explore the substructure of these samples further using STRUCTURE 2.3.2. Re-analysis of the data consistently rejects the existence of an independent coastal Swedish stock in contrast with Svedäng et al. (2018) conclusions. We acknowledge the observation of cod spawning in the area but, based on re-analysis of the original genetic data of Svedäng et al. (2018), we currently lack the scientific basis to assume the existence of established local stocks, and even less the demographic expansion of an older, relict population in the area.